The Significance of Policy Guarantee Institution in Providing Legal Certainty for Insurance Policyholders - Sentosa - Sembiring (Jurnal Wawasan Yuridika, 2023)
This study examined the factors that contributed to the non-establishment of the Policy Guarantee Agency. As stipulated in Article 53, paragraph (4) of Law Number 40 of 2014 concerning Insurance, the formation of the Policy Guarantee Agency was mandated within three years of the enactment of this law. The establishment of this agency held significant importance in furnishing legal safeguards for policyholders. Employing a descriptive research design encompassing normative juridical analysis through statutory and conceptual frameworks, this study regarded secondary data acquired through documentation studies for data collection. The ensuing qualitative analysis of the data revealed that the establishment of the Policy Guarantee Agency necessitated a comprehensive investigation, encompassing considerations such as funding, human resources, and the agency's structural integration, whether as an autonomous entity or as part of an existing Deposit Insurance Corporation. Consequently, achieving consensus among legislative bodies was imperative to advance the establishment of the agency.